Evaluation of the experiences of learners and facilitators with ICT within the realm of higher education - Maiti, Monica; Priyaadharshini, M. (Cogent education, 2024)
The integration of digital instructional methods has significantly enhanced the academic system. This study explores the viewpoints of educators and students on the application of digital resources and online platforms in the aftermath of the global health crisis. The research involved 135 university students enrolled in a cloud computing course that integrated theoretical teaching, practical exercises, and assessments to track their academic progress. Educational sessions were conducted on platforms like Microsoft Teams, Mentimeter, and Padlet, while interactive games were utilized on platforms such as Quizizz and Kahoot. Practical exercises were carried out using Tinkercad. At the end of the semester, the students' academic performance was evaluated using box plots, and a detailed comparison between traditional and digital teaching methods was presented. Results indicated that the majority, approximately 75%, of the students demonstrated better performance when employing digital learning strategies compared to traditional methods. In addition, feedback was gathered through surveys to evaluate the effectiveness of the study, incorporating perspectives from both educators and students for a comprehensive assessment.